Novos espécimes de Arcossauromorfos (Sauria: archosauromorpha) do Triássico inferior da América do Sul e suas implicações filogenéticas - Oliveira, Tiane Macedo de (2019)
Archosauromorpha is defined as the clade that comprises all diapsids more closely related to the lineage of birds (Ornithodira) and crocodilians (Pseudosuchia) than with lepidosaurs. The main objective of this dissertation is to describe new specimens of basal archosauromorphs discovered in Triassic rocks from the Rio Grande do Sul state, Brazil. These materials were recovered in different localities belonging to the Sanga do Cabral Formation. The specimens are represented by isolated cervical vertebrae (UFRGS-PV-492-T, UFRGS-PV-647-T and UNIPAMPA 733) belonging to Universidade Federal do Rio Grande do Sul (UFRGS) and Universidade Federal do Pampa (UNIPAMPA) and a posterior limb with vertebrae and pelvic elements (UFSM 11471), the latter attributed to a new species given by the Universidade Federal de Santa Maria (UFSM). The phylogenetic analysis, reinforced by anatomical comparisons, allowed the attribution of the new specimens to forms related to the clade Tanystropheidae, basal archosauromorphs with distribution between the Early and Late Triassic of Asia, Europe, and North America. Together with other tetrapods already reported for the Sanga do Cabral Formation, this record increases the knowledge of the biotic diversification during the beginning of the Triassic and agrees with previous interpretations in which the tanystropheids originated in a central area of Pangea, possibly in the southwest portion of the Gondwana, and that their ancestors possibly had a terrestrial lifestyle. These new specimens contribute to the knowledge about the diversification of Archosauromorpha after the Permo-Triassic extinction.